2021
DOI: 10.1016/j.ebiom.2021.103211
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two highly antigenic epitope markers predicting multiple sclerosis in optic neuritis patients

Abstract: Background Optic neuritis (ON) can occur as an isolated episode or will develop to multiple sclerosis (MS) a chronic autoimmune disease. What predicts ON progression to MS remains poorly understood. Methods We characterised the antibody epitope repertoire in three independent clinical cohorts (discovery ( n = 62), validation ( n = 20) and external cohort ( n = 421)) using mimotope variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Previous studies have illustrated that CMV or EBV infection may lead to poor prognosis of IIDD and increase the risk of death. Sadam et al 108 reported that patients with NMO who had CMV infection were at a high risk of progressing to MS; thus, CMV viremia could lead to poor prognosis. Similarly, Lünemann et al 109 found that immune reactions to EBV‐encoded nuclear antigen‐1 (EBNA1) could trigger clinically isolated syndromes to convert to MS and suggested that EBNA1‐specific IgG could be used as a prognostic marker for disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have illustrated that CMV or EBV infection may lead to poor prognosis of IIDD and increase the risk of death. Sadam et al 108 reported that patients with NMO who had CMV infection were at a high risk of progressing to MS; thus, CMV viremia could lead to poor prognosis. Similarly, Lünemann et al 109 found that immune reactions to EBV‐encoded nuclear antigen‐1 (EBNA1) could trigger clinically isolated syndromes to convert to MS and suggested that EBNA1‐specific IgG could be used as a prognostic marker for disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The CVD group included samples from patients with chronic coronary artery disease (CAD, n = 32) and with acute coronary syndrome (ACS, n = 32) who were diagnosed by coronary angiography, cardiac enzyme and symptomatic findings 30 (Table S4). The control group (CTRL, n = 402) included samples from individuals with no known history of CAD, ACS or MI and who were either healthy ( n = 125) or had different primary diagnoses ( n = 277) (including gum disease ( n = 25), 30 breast cancer ( n = 57), 31 myasthenia gravis ( n = 129), multiple sclerosis ( n = 20), 32 narcolepsy ( n = 16), 33 or schizophrenia ( n = 30)).…”
Section: Methodsmentioning
confidence: 99%
“…All study samples were analysed using the mimotope-variation analysis method (MVA, 32 , 33 ). In brief, modified random 12-mer peptide phage library (originally derived from Ph.D.-12, New England Biolabs) was amplified according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With another method AMIDA for example, immunoprecipitation is used for separation with subsequent MS analysis [ 90 ]. This is often validated by microarray analyses in which recombinant antigens are incubated with serum, but also using phage displays to detect AAB reactivities against synthesized proteins are prominent [ 91 ]. The first up-regulated AABs identified in the past were AABs against heat shock proteins [ 92 ], gamma-enolase [ 93 ], alpha-fodrin [ 94 ], and myelin basic protein [ 95 ].…”
Section: Diagnosis Of Glaucoma and Screening For Potential Biomarkersmentioning
confidence: 99%